BLASTOCYSTIS HOMINIS INFECTION IN CHILDREN WITH HIV/AIDS DURING COVID-19 RELATED DISRUPTION ERA: A CROSS-SECTIONAL STUDY - Made Bayu Permasutha; Ajib Diptyanusa (The Indonesian Journal of Public Health)
Introduction: The coronavirus disease 2019 (COVID-19) epidemic has resulted in significant disruption to health services in multiple nations. In Indonesia, the impact occurred on changes in services for HIV/AIDS patients. As a result, there is a high rate of parasitic co-infection disease, including Blastocystis hominis. Prior research indicates that the occurrence of this illness varies greatly among individuals with HIV/AIDS, with rates ranging from 3.86% to 72.40%. Aims: The objective of this study is to ascertain the prevalence and molecular epidemiology of infection, develop a predictive model, and examine the correlation between clinical symptoms and the severity of Blastocystis results. Methods: Thirty-eight children with HIV/AIDS in Yogyakarta-Indonesia, from May until August 2021 were examined by direct examination, culture, PCR, and sequencing. In addition, a structured questionnaire was used to obtain additional data regarding baseline information and other factors influencing Blastocystis infection. The results obtained were subjected to phylogenetic, univariate and multivariate data analysis. Results: Out of the 38 samples studied, 26 (68.4%) were positive for Blastocystis. The results of sequencing demonstrated the finding of subtype 3 (ST3) and subtype 4 (ST4).  From univariate and multivariate analysis, a longer duration of therapy is a predictor of Blastocystis infection (AOR 6.54, P=0.04). The relationship between clinical manifestations and intensity of Blastocystis findings showed a non-significant association (P>0.99). Conclusion: Children with HIV/AIDS had a significantly high incidence of Blastocystis infection, potentially attributed to the interruption of services resulting from the COVID-19 pandemic.